Identification of a new potential plasmatic biomarker panel for the diagnosis of malignant pleural mesothelioma - Ferrari, Luca; Iodice, Simona; Cantone, Laura; Dallari, Barbara; Dioni, Laura; Bordini, Lorenzo; Palleschi, Alessandro; Mensi, Carolina; Pesatori, Angela Cecilia (La Medicina del Lavoro, 2022)
Background: Malignant pleural mesothelioma (MPM) is a rare highly aggressive tumor strongly associated with asbestos exposure and characterized by poor prognosis. Currently, diagnosis is based on invasive techniques, thus there is a need of identifying non-invasive biomarkers for early detection of the disease among asbestos-exposed subjects. In the present study, we measured the plasmatic concentrations of Mesothelin, Fibulin-3, and HMGB1 protein biomarkers, and of hsa-miR-30e-3p and hsa-miR-103a-3p Extracellular-Vesicles- embedded micro RNAs (EV-miRNAs). We tested the ability of these biomarkers to discriminate between MPM and PAE subjects alone and in combination. Methods: the study was conducted on a population of 26 patients with MPM and 54 healthy subjects with previous asbestos exposure (PAE). Mesothelin, Fibulin-3, and HMGB1 protein biomarkers were measured by the enzyme-linked immunosorbent assay (ELISA) technique; the levels of hsa-miR-30e-3p and hsa-miR-103a-3p EV-miRNAs was assessed by quantitative real-time PCR (qPCR). Results: the most discriminating single biomarker resulted to be Fibulin-3 (AUC 0.94 CI 95% 0.88-1.0; Sensitivity 88%; Specificity 87%). After investigating the different possible combinations, the best performance was obtained by the three protein biomarkers Mesothelin, Fibulin-3, and HMGB1 (AUC 0.99 CI 95% 0.97-1.0; Sensitivity 96%; Specificity 93%). Conclusions: the results obtained contribute to identifying new potential non-invasive biomarkers for the early diagnosis of MPM in high-risk asbestos-exposed subjects. Further studies are needed to validate the evidence obtained, in order to assess the reliability of the proposed biomarker panel.